2019
DOI: 10.1002/wcs.1515
|View full text |Cite
|
Sign up to set email alerts
|

Developmental sociolinguistics: Children's acquisition of language variation

Abstract: Developmental sociolinguistics is a rapidly evolving interdisciplinary framework that builds upon theoretical and methodological contributions from multiple disciplines (i.e., sociolinguistics, language acquisition, the speech sciences, developmental psychology, and psycholinguistics). A core assumption of this framework is that language is by its very nature variable, and that much of this variability is informative, as it is (probabilistically) governed by a variety of factors—including linguistic context, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 112 publications
(163 reference statements)
2
23
0
Order By: Relevance
“…Evidence for this general tendency comes from studies of lexical and phonological variation, as well as morphosyntactic variation. For instance, in their study of 29 children in Buckie, Scotland, ages 2;10 to 4;2, Smith and Durham (2019) found that the 2;10-3;1-year-olds primarily produced standard lexical and lexicalphonological forms like pretty and what, whereas the 3;2-4;2-year-olds varied between standard and local forms like pretty ~ bonnie and what ~ fit (See also Johnson & White, 2020). Miller (2013a) also found that children first relied on one variant in her study of 2-5-year-old Chilean children's syllable final /s/ lenition.…”
Section: Step 1: Sequential Learning Of Forms In Variationmentioning
confidence: 99%
“…Evidence for this general tendency comes from studies of lexical and phonological variation, as well as morphosyntactic variation. For instance, in their study of 29 children in Buckie, Scotland, ages 2;10 to 4;2, Smith and Durham (2019) found that the 2;10-3;1-year-olds primarily produced standard lexical and lexicalphonological forms like pretty and what, whereas the 3;2-4;2-year-olds varied between standard and local forms like pretty ~ bonnie and what ~ fit (See also Johnson & White, 2020). Miller (2013a) also found that children first relied on one variant in her study of 2-5-year-old Chilean children's syllable final /s/ lenition.…”
Section: Step 1: Sequential Learning Of Forms In Variationmentioning
confidence: 99%
“…In the past 50 years, we have learned a great deal about the remarkable efficiency with which the typical infant masters their native language or languages (see Johnson and White, 2020;Swingley, 2009;Werker and Curtin, 2005 for an overview). Crucially for the purposes of this review, however, most of this work has involved presenting infants with stimuli spoken in the regionally dominant variety of the child's native language.…”
Section: A Chronological View Of Developmentmentioning
confidence: 99%
“…Artificial language learning experiments have demonstrated that children tend to regularize input that varies unsystematically (Hudson Kam & Newport, 2005) but that they are able to learn the probabilistic regularities of socially conditioned language variation (Samara et al, 2017). Thus, acquiring patterns of variation is an integral and manageable part of language acquisition, which starts early and occurs (at least in part) simultaneously with other aspects of language acquisition (Johnson & White, 2020). At the same time, while linguistic and socio-indexical knowledge are likely to be acquired in parallel, the development of sociolinguistic competence is a prolonged process that takes years (Dossey et al, 2020).…”
Section: Bi-and Multidialectal Language Acquisition In Childrenmentioning
confidence: 99%